Franchising - Judd, Richard; Justis, Robert T. (Cincinnati : South-Western, 1998)
This book is about: History and overview of franchising; Recognizing franchising opportunities; The Franchise plan; Management, organization and administrative policy; ...
Keywords: Management; Retail trade; Franchises; Franchises (Retail trade) -- United States; Franchises (Retail trade) -- Law and legislation -- United States